2022
DOI: 10.1161/strokeaha.122.039790
|View full text |Cite
|
Sign up to set email alerts
|

Glenzocimab: A GPVI (Glycoprotein VI)-Targeted Potential Antiplatelet Agent for the Treatment of Acute Ischemic Stroke

Abstract: It has previously been shown in several animal experiments that platelet GPVI (glycoprotein VI) contributes to thrombosis, particularly in ischemic stroke. Moreover, GPVI levels are upregulated in stroke patients. This review describes the therapeutic roles of anti-GPVI antibody in preclinical models of ischemic stroke and provides the current evidence for potential benefits of glenzocimab, a Fab fragment of humanized anti-GPVI monoclonal antibody, in stroke patients. Anti-GPVI antibody, JAQ1, significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 50 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…22 Platelets might interact with collagen through their receptors with GP (glycoprotein) Ib/V/IX as previously reported. 23 Whether targeting GP Ib/V/ IX can prevent platelet activation in the stiff regions of the thrombus and change the composition of the thrombus await future study. In addition, platelet activation promotes inflammation which contributes to the interaction of platelets with endothelial cells and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…22 Platelets might interact with collagen through their receptors with GP (glycoprotein) Ib/V/IX as previously reported. 23 Whether targeting GP Ib/V/ IX can prevent platelet activation in the stiff regions of the thrombus and change the composition of the thrombus await future study. In addition, platelet activation promotes inflammation which contributes to the interaction of platelets with endothelial cells and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory involvement of platelets in stroke is thought to be mediated via GPVI, as well as the VWF A1-GPIbα axis, but not α IIb β 3 [ 72 , 73 , 74 ]. In line with this, recent clinical trials with GPVI antagonists showed promising outcomes in the treatment of acute ischemic stroke [ 75 , 76 , 77 ]. Neutrophils were detected within hours of stroke onset and their numbers correlated with the infarct size in humans and mice [ 78 , 79 , 80 ].…”
Section: Arterial Thrombosismentioning
confidence: 77%
“…To emphasize rapid interventions, which help prevent neuronal loss during ischemic stroke, the phrase “time is brain” is widely used . Nevertheless, the success rate for complete re-canalization following intravenous thrombolytic therapy is less than 50%, suggesting the need for novel therapeutic agents . A genetic study reported that the CG/GG genotypes of the FURIN rs2071410 SNP are associated with ∼50% increased risk of transient ischemic attack (TIA), compared with the homozygous CC genotype (Table ).…”
Section: Ischemic Strokementioning
confidence: 94%
“…129 Nevertheless, the success rate for complete re-canalization following intravenous thrombolytic therapy is less than 50%, suggesting the need for novel therapeutic agents. 130 A genetic study reported that the CG/ GG genotypes of the FURIN rs2071410 SNP are associated with ∼50% increased risk of transient ischemic attack (TIA), compared with the homozygous CC genotype (Table 2). 95 This SNP potentially contributes to a reduction in furin activity and an increase in hypertension, 35 a strong associated risk factor of TIA.…”
Section: ■ Ischemic Strokementioning
confidence: 99%